2013
DOI: 10.1007/s13277-013-0694-2
|View full text |Cite
|
Sign up to set email alerts
|

Loss of WIF-1 and Wnt5a expression is related to aggressiveness of sporadic breast cancer in Tunisian patients

Abstract: Activation of the Wnt/β-catenin signaling pathway is common in various human cancers. The aim of this study was to investigate the expression of 2 members of the Wnt family (WIF-1 and Wnt5a) in sporadic and hereditary breast cancer tissues. WIF-1, is a secreted antagonist that binds Wnt ligands, and therefore inhibits the canonical Wnt/β-catenin pathway. Wnt5a is one of the members of the noncanonical Wnt family that mainly acts through calcium signaling pathway. The expression of WIF-1 was analyzed by methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In patients with ER-negative disease, lower levels of WNT5A are significantly associated with worse clinical outcome. These results are in accordance with those of Trifa et al in Tunisian patients [22]. …”
Section: Expression and Function Of Wnt5a In Breast Cancersupporting
confidence: 93%
“…In patients with ER-negative disease, lower levels of WNT5A are significantly associated with worse clinical outcome. These results are in accordance with those of Trifa et al in Tunisian patients [22]. …”
Section: Expression and Function Of Wnt5a In Breast Cancersupporting
confidence: 93%
“…However, the manner in which WNT signaling pathways and their inhibitors function together during cancer progression remains unclear. Whereas APCDD1 expression is negatively associated with invasion, WIF, DKK and SFRP are epigenetically inactivated in breast cancer cells, independent of invasion (28,29). Therefore, different WNT signaling pathway inhibitors may serve crucial functions in the multiple roles of the canonical WNT signaling pathway in breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…21 Others have shown that WIF1 promoter hypermethylation correlates with loss of p53 expression. 60 p53 has been shown to regulate the expression of Wnt genes and suppress the Wnt/ β -catenin signaling. 61, 62 Our data suggest for the first time the existence of a positive feedback by which WIF1 regulates the expression of p53.…”
Section: Discussionmentioning
confidence: 99%